Divergent Floral and Vegetative Trait Responses to Abiotic Factors Drive Phenotypic Diversity in Platanthera dilatata (Orchidaceae) Across Alaska - Marlin L. Bowles; Lisa E. Wallace (Ecology and Evolution, 2025)
ABSTRACT Multiple traits make up an integrated phenotype, but traits may be shaped by differing drivers. It is often assumed that selection by biotic agents drives floral variation, but abiotic factors are also known to influence floral traits. Understanding trait covariations and their association with diverse environmental factors is a central question in evolution and ecology. Here, we studied covariation in floral and vegetative traits in relation to climate and topo‐edaphic variation in the orchid Platanthera dilatata. In Platanthera, nectar spur length is associated with pollinator tongue length, but much variation exists in other traits too, likely to be influenced by abiotic factors. We analyzed floral, inflorescence, and leaf measures from 146 digital herbarium specimens of P. dilatata collected in Alaska, USA, and nearby areas, asking whether phenotypic variation occurred across regions and habitats and how abiotic factors affect these patterns. Our results suggest a continuum of multi‐trait variation in P. dilatata and suggest that individual traits may be under contrasting influence by the regional climate, local topo‐edaphic conditions, and pollinator‐mediated selection. Phenotypes were distributed among geographic regions, as well as habitats. Plants with larger leaves, inflorescences, sepals, and lips tended to predominate in coastal meadows with moderate climates, while those with smaller traits tended to predominate in continental wet meadows with extreme climates, as well as fens and muskeg bogs. Nectar spur length was poorly correlated with leaf, inflorescence, and flower size and had lower correlations with climatic factors, suggesting that spurs respond to other factors. Differentiating among varieties by spur–lip length relationships may be problematic because of continuous independent variation in both traits. Understanding the mechanisms that generate phenotypic variation in P. dilatata would benefit from studies of the underlying genetic control, propensity for phenotypic plasticity across traits, and historical perspectives on the relationships of populations with similar phenotypes.